Research and Innovation Strategic Alliance of Cedars-Sinai Medical Center and Central – Eastern European (CEE) Academic Organizations - Vari, S.G.; Laur, J.D. (Наука та інновації, 2005)
In 2000 Cedars!Sinai Medical Center (CSMC) has developed the "Innovation Management and Technology Transfer Training" (IMTT) Program and in 2004 the "Research and Innovation Management Training" (RIMET) Program to train scientists, physicians and healthcare managers at CSMC and in Central ! Eastern European (CEE) Countries in research and technology transfer management. CSMC believes that it is essential for its partner universities to have the ability to protect the intellectual advances that arise from their laboratories and to negotiate commercially appropriate licensing deals. The IMTTTM and RIMETTM programs educate and train managers in research, innovation management, business development, and licensing to build a robust intellectual property portfolio and incorporate the institutional patent portfolios into a "Joint Patent Portfolio" (JPP) to connect academic organizations throughout CEE in an "Intellectual Property WarehouseTM" (IPWTM).